A research analysis on the effectiveness of banana pseudostem fiber and sawdust in absorbing sound and controlling sound transmission - Vosotros, Katherine A.; Juanga, Jean Marie V. (2015)
The study investigated the acoustic characteristics of organic materials such as banana pseudostem fiber and sawdust. Banana pseudostem fibers are fibers which can be extracted from the banana pseudostem. Banana pseudostems are waste materials after harvesting. On the latter, sacks of sawdust are leftovers produced in wood processing. These are common organic waste materials which contribute to the increasing volume of waste produced in the country every year which is considered as one of the major factors that causes environmental degradation. On the hand, typical acoustic materials which are commercially available such as made from mineral fibers have been associated to potential health risk due to its handling process. These issues provide an opportunity to investigate some organic fibers as alternative acoustical material in construction industry. During the processing stage, the banana fiber and sawdust were first dried in order to remove its moisture content, the banana fibers were cut into desired sizes and sawdust were sieved. The fiber particles were then mixed proportionally together with a specific amount of water and Plaster of Paris, which served as the binding agent of the material. The experimental data where obtained using the Diffuse-field Sound Absorption model or the Reverberation test method to get the reverberation time data and Diffuse-field Sound Transmission model to determine the noise reduction between two adjacent spaces (source and receiving room ). The reverberation time were used in calculating for the sound absorption coefficient of the material per sound frequency. The Noise reduction coefficient was then determined by getting the average sound absorption coefficient. On the other hand, the noise reduction was used to calculate for the sound transmission loss index and sound transmission class rating of the material. The results showed that the Banana Pseudostem Fiber and Sawdust Particleboard got an NRC of 0.86 metric Sabine, thus is considered very effective in terms of absorbing sound. This is comparable to the NRC rating of the Glass Fiber Ceiling Tile and 2-inch thick Fiber glass wall panel. On the other hand, the Banana Pseudostem Fiber and Sawdust Particleboard got an STC of 0.46 decibels which is the same with the STC rating of a 100 mm timber studs with plasterboards at both sides and a quilt or 3-layer fiber blanket. From the given results, the researcher was able to conclude that the Banana Pseudostem Fiber and Sawdust Particleboard is effective in absorbing sound and controlling sound transmission. However, the fire rating resistivity and life expectancy of the material can also be subjected for further research. Further studies and development of the material may further enhance the performance of the material.
Thesis (BS Architecture) -- University of the Philippines Mindanao, 2015